The Italian Piazza Transformed : Parma in the Communal Age - Marina, Areli, 1964- (Book collections on Project MUSE., 2012)
"Explores the history and architecture of two city squares, constructed by rival political parties, in the Italian city of Parma from 1196 to 1300"--Provided by publisher.